A Study of CGTMSE Plan and Strategy to Profit in Bank Finance to MSE Sector: Designing a Strategy for Profitable MSME Lending in Indian Banks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Rising capital requirements and NPAs are impediments to large lending by Indian banks and thereby their profitability. Indian banks, therefore, need to design strategy for their profitable growth through MSME lending. For successful lending to MSME, sector specific approach is required by banks. Different approach is required for manufacturing enterprise and service enterprise. Banks need to innovate and modify the financial products which are best suitable to them, and also design risk management strategy for MSME lending. CGTMSE has grasped multi-channel approach for making awareness of the CGS among banks, MSE industry affiliations, MSE division, et cetera through print and press media, coordinating workshopscourses, setting off to the projects dealt with at different regionstatenational for a, and so on. Amid the year, CGTMSE took an interest in different classesworkshops sorted out by MLIs and Industry Associations, presentations and gatherings composed by RBIGovt. regarding MSE part, the nation over to make mindfulness about CGS. CGTMSE specialists similarly held business progression social affairs with its Member Lending Institutions. Overseen print media fights were finished the country over amid an opportunity to improve detectable quality and make mindfulness about the plan. Data dispersal battles were enthusiastically done among different partners.